2020
DOI: 10.1186/s12199-020-00855-8
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach to assess the toxicities of arsenic and barium in drinking water

Abstract: Well water could be a stable source of drinking water. Recently, the use of well water as drinking water has been encouraged in developing countries. However, many kinds of disorders caused by toxic elements in well drinking water have been reported. It is our urgent task to resolve the global issue of element-originating diseases. In this review article, our multidisciplinary approaches focusing on oncogenic toxicities and disturbances of sensory organs (skin and ear) induced by arsenic and barium are introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 74 publications
0
11
0
5
Order By: Relevance
“…Intake of arsenic from well drinking water has been shown to be an important health risk for people in developing countries (Kato et al, 2020;Kumasaka et al, 2013;Li et al, 2017;Yajima et al, 2018;Yajima et al, 2015). The aim of our study was to elucidate the health risk of arsenic from dietary intake in Japan.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Intake of arsenic from well drinking water has been shown to be an important health risk for people in developing countries (Kato et al, 2020;Kumasaka et al, 2013;Li et al, 2017;Yajima et al, 2018;Yajima et al, 2015). The aim of our study was to elucidate the health risk of arsenic from dietary intake in Japan.…”
Section: Discussionmentioning
confidence: 96%
“…Those studies indicate that there is a strong contribution of elements such as sodium and potassium via food intake to the prevalence of hypertension. Arsenic (As) is known as a representative toxic element (Kato et al, 2020;Li et al, 2018;Yajima et al, 2017). Various arsenic-mediated health risks including risks for oncogenic, neurogenic and cutaneous disorders have been reported (Li et al, 2017;Yajima et al, 2018;Zhong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic is found in food, water, soil, and air, with a common method of exposure being the inhalation of dusts. 35 Islam et al 36 reported on the arsenic content of certain dental materials. Studies on arsenic trioxide in coronary stents have provided toxicological information for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out with experimental animals show that B affects development, and the reproductive system and V can cause kidney damage (IOM, 2001). Ba is an element that acts as an antagonist of K and Ca and tends to accumulate in bones (Kato et al, 2020). Ni is an element that can cause dermatitis, especially harmful in individuals with hypersensitivity or kidney problems (Das et al, 2018).…”
Section: Introductionmentioning
confidence: 99%